Can bacterial lysates be useful in prevention of viral respiratory infections in childhood? The results of experimental OM-85 studies - Ballarini, Stefania; Ardusso, Ledit; Ortega Martell, José Antonio; Sacco, Oliviero; Feleszko, Wojciech; Rossi, Giovanni A. (Frontiers in Pediatrics, 2022)
Respiratory tract infections (RTI) are mainly viral in origin and among the leading cause of childhood morbidity globally. Associated wheezing illness and asthma are still a clear unmet medical need. Despite the continuous progress in understanding the processes involved in their pathogenesis, preventive measures and treatments failed to demonstrate any significant disease-modifying effect. However, in the last decades it was understood that early-life exposure to microbes, may reduce the risk of infectious and allergic disorders, increasing the immune response efficacy. These results suggested that treatment with bacterial lysates (BLs) acting on gut microbiota, could promote a heterologous immunomodulation useful in the prevention of recurrent RTIs and of wheezing inception and persistence. This hypothesis has been supported by clinical and experimental studies showing the reduction of RTI frequency and severity in childhood after oral BL prophylaxis and elucidating the involved mechanisms. OM-85 is the product whose anti-viral effects have been most extensively studied in vitro, animal, and human cell studies and in translational animal infection/disease models. The results of the latter studies, describing the potential immune training-based activities of such BL, leading to the protection against respiratory viruses, will be reported. In response to human rhinovirus, influenza virus, respiratory syncytial virus and severe acute respiratory coronavirus-2, OM-85 was effective in modulating the structure and the functions of a large numbers of airways epithelial and immune cells, when administered both orally and intranasally.